Immersive learning laboratory in health and nursing: learning biosafety in a virtual world - Karen Cardoso; Milton Antônio Zaro; Ana Maria Muller de Magalhães; Liane Margarida Rockenbach Tarouco
ABSTRACT Objectives: to develop a virtual simulation and learning laboratory in an immersive virtual world that enables students, nursing professionals as well as health professionals to experiment, reflect and contextualize biosafety actions, infection protection concepts and universal precautions. Methods: description of the development of the Immersive Learning Laboratory in Health and Nursing (LIASE) with a focus on biosafety, having as theoretical basis Kolb's experimental learning cycle and the OpenSimulator platform. Results: development of the Immersive Learning Laboratory in Health and Nursing: Health Biosafety Module - contains five learning stations. Final Considerations: the development of LIASE indicates the possibility of supporting face-to-face learning in a practical laboratory and continuing the study and implementation with the target audience.